STUDI KOMPARATIF ANTARA HADIS LARANGAN BERJUDI DAN HUKUM POSITIF DI INDONESIA - Bisri Tujang; Hendri Waluyo Lensa; Muthalib, Abd. (Al-Majaalis : Jurnal Dirasat Islamiyah, 2025)
Online gambling has emerged as a pervasive social issue in Indonesia, causing detrimental impacts across psychological, economic, and social dimensions. This study examines a comparative analysis between the understanding of the hadith prohibiting gambling and Indonesia's positive legal regulations to identify effective solutions for eradicating online gambling. Data reveals national economic losses exceeding 900 trillion rupiah since 2021, with 2% of online gamblers being underage children. The research employs qualitative analysis through a literature study and normative approach. The findings indicate that both Islamic law and positive law prohibit and penalize gambling, although differences exist in the focus of their enforcement. This study recommends enhanced public education, job creation, and stricter legal enforcement against key players in the online gambling chain. Spiritually, increasing religious awareness is crucial to combating this chronic social disease.